Prevention of shoulder injuries in swimmers - Gracanin, I.; Djurovic, M.; Gracanin, J.; Stanic, D.; Burhaein, E.; Demirci, N.; Singh, R. R. M.; Koliopoulos, T.; Skrypchenko, I. (International Journal of Academic Health and Medical Research, 2023)
Abstract: The aim of this research was to examine and point out the prevention of sports injuries in swimmers. Swimming training involves repetitive movementsshoulders that provide propulsive forces by using the arms as oars to propel the body through the water.Overtraining in swimming causes muscle fatigue that can lead to reduced rotator cuff efficiency and ineffective positioning of the scapula during each stroke. Another major risk factor for swimmers and shoulder injury is muscle imbalance that leads to shoulder instability, which results from ligamentous laxity and increased range of motion. the most commonly used are:external rotation,lifting a full bucket, raising arms with a full bucket,ball to the wall, rowing with an elastic band, auto-stopper, push-ups with one addition. It can be concluded that coaches have a very big role in recognizing, but also in the preventive action of shoulder injuries through monitoring the training load, correcting certain segments of swimming technique (swimming stroke), as well as strengthening and muscle stretching in the so-called "dry" training for swimmers.